2001
DOI: 10.1159/000050688
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome in Mexico

Abstract: The current review includes all the available original data on irritable bowel syndrome in Mexico. Data were organized in items of interest such as prevalence and gender distribution, health care utilization, psychosocial factors, diagnostic criteria, bowel habit predominance, physiological studies, clinical trials and quality of life assessment. After a systematic review, a total of 18 papers were included, the majority published between 1996 and 2000. We can conclude that irritable bowel syndrome in Mexico i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
6
0
3
Order By: Relevance
“…In Mexico, previous small studies using different criteria have shown a preva-lence range from 14 to 20% and a female:male ratio of 2.5: 1.0 [1] . In the current study using the Rome II criteria, we found an unexpected high frequency of IBS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Mexico, previous small studies using different criteria have shown a preva-lence range from 14 to 20% and a female:male ratio of 2.5: 1.0 [1] . In the current study using the Rome II criteria, we found an unexpected high frequency of IBS.…”
Section: Discussionmentioning
confidence: 94%
“…Previous limited studies utilizing the Manning criteria and the Rome I criteria suggest that irritable bowel syndrome (IBS) has a prevalence that ranges between 17 and 20% in selected populations in Mexico [1] . Little is known about the prevalence of the functional bowel disorders (FBD) utilizing the Rome II criteria [2] .…”
Section: Introductionmentioning
confidence: 99%
“…En países industrializados se ha descrito una prevalencia entre el 10 y el 15% y en países latinoamericanos, como Brasil, México y Uruguay, entre el 9 y el 18% [22][23][24][25][26] , pero no son comparables con este estudio, ya que utilizan los criterios de Roma II. En Colombia los estudios epidemiológicos son escasos, entre ellos se encuentra un estudio del Servicio de Gastroenterología del Hospital Universitario de la Samaritana de Bogotá, el que observó una prevalencia del 14% de 7.000 consultas realizadas por año 5 ; además, un estudio en trabajadores formales del servicio hospitalario del Hospital San Juan de Dios de Bogotá, que mostró una prevalencia del 12,5% (IC del 95%: de 7,8 a 17,2) según los criterios de Roma II 24 .…”
Section: Discussionunclassified
“…Irritable bowel syndrome (IBS) is the most frequent functional gastrointestinal disorder with a frequency among the world population that varies from 5-25% [1,2]. It is the first reason for consultations to gastroenterologists and the fourth most common gastrointestinal-related outpatient diagnosis among internal medicine and general practice physicians [3,4].…”
Section: Introductionmentioning
confidence: 99%